Error annotation in a Learner Corpus of Portuguese - Mendes, Amália (2019)
We present the error tagging system of the COPLE2 corpus and the first results of its implementation.. The system takes advantage of the corpus architecture and the possibilities of the TEITOK environment to reduce manual effort and produce a final standoff, multilevel annotation with position-based tags that account for the main error types observed in the corpus. The first step of the tagging process involves the manual annotation of errors at the token level. We have already annotated 47% of the corpus using this approach. In a further step, the token-based annotations will be automatically transformed (fully or partially) in position-based error tags. COPLE2 is the first Portuguese learner corpus with error annotation. We expect that this work will support new research in different fields connected with Portuguese as second/foreign language, like Second Language Acquisition/Teaching or Computer Assisted Learning.